2018
DOI: 10.11648/j.wjph.20180303.12
|View full text |Cite
|
Sign up to set email alerts
|

Premarital Sickle Cell Genetic Screening Knowledge, Attitude and Practice Compared Among Married and Unmarried Youths in Nigeria

Abstract: Premarital sickle cell genetic screening is a test that determines the genotype of the intending couple before marriage. As a result, counseling is given before and after the test. This study assessed and compared the level of knowledge, attitude and practices of premarital sickle cell screening among married and unmarried youths in Epe, Nigeria. A crosssectional descriptive research design was used to examine 370 participants, using stratified sampling technique. Data were collected with an instrument and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[41][42][43] Level of education has been reported as a determinant of good knowledge about sickle cell disease. 44,45 A cross-sectional survey by Rasheed et al 46 on married and unmarried youths in Nigeria revealed that the level of knowledge of participants was good (70.06%); however, participants had negative attitudes towards the practice of premarital sickle cell genetic screening. The findings from that study were attributed to inadequate public health awareness and lack of basic knowledge on the haemoglobin genotype and sickle cell disease.…”
Section: Knowledge About Sickle Cell Diseasementioning
confidence: 99%
“…[41][42][43] Level of education has been reported as a determinant of good knowledge about sickle cell disease. 44,45 A cross-sectional survey by Rasheed et al 46 on married and unmarried youths in Nigeria revealed that the level of knowledge of participants was good (70.06%); however, participants had negative attitudes towards the practice of premarital sickle cell genetic screening. The findings from that study were attributed to inadequate public health awareness and lack of basic knowledge on the haemoglobin genotype and sickle cell disease.…”
Section: Knowledge About Sickle Cell Diseasementioning
confidence: 99%